The political economy of food and nutrition policies - Pinstrup-Andersen, Per (International Food Policy Research Institute, 1993)
Few nutritionists and economists fully appreciate how the political environment shapes policy and subsequently affects the relevance of their policy recommendations... When governments fail to follow the recommendations of nutritionists and economists and are unable to design and implement cost-effective nutrition programs and policies, it is often attributed to "politics" or to lack of "political will" on the part of decisionmakers... Past nutrition planning efforts frequently failed to understand the goals and behavior of the various agents and institutions inside and outside the government that, in the final analysis, determine whether the planning effort is successful...In The Political Economy of Food and Nutrition Policies, Per Pinstrup-Andersen brings together a group of distinguished authorities to improve the understanding of how nutrition policies are formulated within larger political and economic contexts and how public-sector agencies behave with regard to food and nutrition.